Urinary tract infection in primary care: state of the art - Machado, Gabriela (2022)
Introduction: Urinary tract infection (UTI) is the second most prevalent infection in the community. Aims: To determine the microorganisms responsible for UTI in Primary Health Care and their profile of sensitivity to antibiotics, as well as to evaluate if the approach of the UTI is concordant with the National Health Authority’s recommendations. Methods: Observational and retrospective study in four primary health care centers in Almada. Patients aged 18 years or older, whose appointments were coded with ICPC-2’s problems (U71-Cystitis/Urinary Infection Other and U70-Pyelonephritis/Pyelitis) between July and December 2019 were included. The SClínico software and the MIMUF platform were chosen to collect data. The variables studied were: sex, age, type of UTI, urine culture request, empirical antibiotics, the result of urine culture, and antimicrobial sensitivity test. Results: Of the 963 UTIs, 88.3% occurred in women, mainly between 68 and 77 years old (18.9%). The most prevalent type of UTI was uncomplicated cystitis in non-pregnant women (56.3%). Empirical antibiotic therapy was prescribed in 86.7% of the cases, with fosfomycin being the most used one (58.6%). Four hundred and five urine culture requests were made, most of them with a positive result. E. coli was the most frequently identified microorganism (66.4%), being the most prevalent in all age groups and in the different types of UTI. It was sensitive to fosfomycin in 63.7% of cases. In the global analysis of the different units, it was found that urine culture was in accordance with the national recommendation in 70.4% of the cases and that empirical antibiotics were in accordance in 63% of the UTI cases. Conclusions: UTIs in the community are more frequent in women between 68 and 77 years old. The most prevalent bacterial microorganism is E.coli, with significant sensitivity to fosfomycin and nitrofurantoin.